Economic and Mindfulness-Based Interventions for Lecturers’ Resilience fnd Well-Being in Higher Education in Nigeria (West African Journal on Sustainable Development, 2024)
Background: Lecturers in higher education face significant pressures, often leading to burnout and decreased well-being. Mindfulness-based interventions have shown promise in promoting resilience and well-being in various professions.Purpose: This study investigates the effectiveness of economic and mindfulness-based interventions in enhancing lecturer well-being and resilience within higher education institutions.Method: A sample of 360 lecturers purposively selected from different department participated in a randomized controlled trial. The intervention group received a mindfulness-based training program, while the control group received a waitlist intervention. Surveys measuring well-being and resilience was administered before and after the training program (intervention group) and at corresponding points for the control group. Quantitative and qualitative data analysis was conducted using inferential statistics to assess pre-post intervention changes within the intervention group compared to the control group. Qualitative data collected through open-ended surveys or interviews, was analyzed thematically using SPSS 25 to explore participants' experiences with the intervention and its impact.Findings: The findings reveal that lecturers’ who participate in the mindfulness-based training program report improvements in well-being and resilience compared to the control group. In addition, it reveals that economic interventions such as Providing financial support for research projects, offering childcare education subsidies, among others help to reduce financial stress and improves the internal well-being practices of lecturers. Additionally, qualitative data reveal deeper insights into how mindfulness practices contribute to these positive changes. This research has the potential to inform the development of evidence-based strategies to support lecturer well-being and create a more sustainable work environment in higher education.Recommendations: The study recommends that institutions should occasionally organize a mental assessment training for lecturers’ occasionally, while ensuring that the welfare package of the lecturers’ are looked into so as to increase the level of their assertiveness in carrying out their duties.
Keywords: Economic; Mindfulness; Lecturers’ Resilience; Wellbeing; Higher Education